LA GESTION RATIONNELLE ET DYNAMIQUE DU TRAVAIL DANS LES ENTREPRISES PUBLIQUES TRANSFORMEES EN SOCIETES COMMERCIALES PAR LA LOI N°09/007 DU 07 JUILLET 2018 ET LE DECRET N°09/ 12 DU 24 AVRIL 2009 EN REPUBLIQUE DEMOCRATIQUE DU CONGO. Cas de la Société Congol - James LOHOMBOLI LOLA; Ibrahym KATHY MBIYE; Didier OMADJELA MBIDI; Josué KATANDA FUNDI (IJRDO - Journal of Business Management, 2020)
The socio-economic environment of public enterprises transformed into commercial companies like the Congolese Post and Telecommunications Society in acronym "SCPT", then Congolese Post and Telecommunications Office ex OCPT in acronym, in the City of Kisangani, shows a significant drop in production linked to irrational management due to several reasons listed under study. The ultimate objective of Rational and Dynamic Management of Work in acronym GRDT in a company such as tackling all of this research remains without a doubt the growth of productivity for the maximization of profit with a view to economic development and economic agent in its entirety. At the end of this work, our investigations demonstrated the micro and macro-economic paradox in the professional life of managers and agents as well as the future of this firm. Long squatting economically and devoid of managerial strategies for its socio-economic growth in the current context of competitiveness and sustainability of services, like other private companies with the same commercial monopoly, there is obviously work to be done for Rational and Dynamic Work Management in this commercial enterprise. Therefore, the GRDT being non-existent at the SCPT, it is imperative to set up the managerial mechanisms likely to develop this society economically and socially.